2021
DOI: 10.1088/1755-1315/686/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the land use/land cover influence on land surface temperature in San Luis Potosí Basin, México using remote sensing techniques

Abstract: Changes in Land Use/Land Cover (LULC) generate several impacts which affect the energy balance of the Earth and, consequently, modifying the climate of a region. Accordingly, one of the most important indicators of this modification is the Land Surface Temperature (LST). The present work aims to analyze the relationship between LULC and LST, determining the influence of LULC on LST using Geographical Information Systems (GIS) and Remote Sensing (RS) techniques. The selected study area was the San Luis Potosí B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…On the other hand, in this study, it was found that the city's impermeable materials have the highest values of net flux, meaning that, in these areas, the energy cannot be used for the evapotranspiration processes, causing an increase in the temperature of the city. According to Ovalle et al [25], it has been verified that the surfaces with coverage without vegetation and urban areas tend to have higher temperatures in the study area. Likewise, the study area has presented climatic changes related to soil cover [25,26].…”
Section: Net Radiation Changes Implicationsmentioning
confidence: 77%
See 2 more Smart Citations
“…On the other hand, in this study, it was found that the city's impermeable materials have the highest values of net flux, meaning that, in these areas, the energy cannot be used for the evapotranspiration processes, causing an increase in the temperature of the city. According to Ovalle et al [25], it has been verified that the surfaces with coverage without vegetation and urban areas tend to have higher temperatures in the study area. Likewise, the study area has presented climatic changes related to soil cover [25,26].…”
Section: Net Radiation Changes Implicationsmentioning
confidence: 77%
“…According to Ovalle et al [25], it has been verified that the surfaces with coverage without vegetation and urban areas tend to have higher temperatures in the study area. Likewise, the study area has presented climatic changes related to soil cover [25,26]. Several analyses registered similar behaviors [27][28][29], where the energy depends on the ground cover.…”
Section: Net Radiation Changes Implicationsmentioning
confidence: 77%
See 1 more Smart Citation
“…Hamdi et al [30] have argued that the LST of Belgium has been rising at the rate of 0.15 • C for every decade since 1960 due to urbanization. Ovalle et al [31] have reported an increase of approximately 11 • C in LST due to land cover changes (LCCs) in Luis Potosi, Mexico, in the last two decades. Using the Landsat series data, Jalan et al [32] noted that the LST has increased from about 2.9 • C to 4.0 • C in Jaipur, India.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Maishella et al's [5] study aimed to analyze the changes in LC (built-up area) and its relationship with LST in Sleman Regency; results indicated a positive relationship between the increase in the built-up areas and an increase in LST. Ovalle et al [6] studied the relationship between LULC and LST using the geographical information systems (GIS) and RS in the San Luis Potosí Basin, México. The results showed an opposite relation between vegetation cover density and LST; the less vegetation cover, the higher the LST.…”
Section: Introductionmentioning
confidence: 99%